2010
DOI: 10.1007/s10151-010-0649-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional evaluation of patients with rectocele and mucosal prolapse treated with transanal repair of rectocele and rectal mucosectomy with a single circular stapler (TRREMS)

Abstract: BackgroundThe aim of the present study was to make a preoperative and postoperative clinical and functional evaluation of patients who underwent transanal repair of rectocele and rectal mucosectomy with a single circular stapler (TRREMS procedure) as treatment for obstructed defecation syndrome (ODS) caused by rectocele and rectal mucosal prolapse (RMP).MethodsThis prospective study included 35 female patients, 34 multiparous and one nulliparous, with an average age of 47.5 years (range 31–67 years), rectocele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…in a prospective multicenter study of 75 patients with anorectocele associated with mucosal prolapse or rectal intussusception, 20 the mean agachan-Wexner constipation score decreased significantly (from 16 to 4; p = 0.001), and the authors concluded that the tRRems procedure is a safe and effective technique, capable of restoring the anatomic integrity of the anal canal. another study 21 in patients with grade ii or iii rectocele also demonstrated significant reductions in the mean constipation score (from 15.23 to 4.46; p = 0.001) and in the mean obstructed defecation score 12 (from 10.6 to 2.9; p = 0.001) with the tRRems procedure. Compared with staRR, the tRRems procedure has the advantage of lower costs because it requires only 1 circular stapler.…”
Section: Technical Notesmentioning
confidence: 83%
See 1 more Smart Citation
“…in a prospective multicenter study of 75 patients with anorectocele associated with mucosal prolapse or rectal intussusception, 20 the mean agachan-Wexner constipation score decreased significantly (from 16 to 4; p = 0.001), and the authors concluded that the tRRems procedure is a safe and effective technique, capable of restoring the anatomic integrity of the anal canal. another study 21 in patients with grade ii or iii rectocele also demonstrated significant reductions in the mean constipation score (from 15.23 to 4.46; p = 0.001) and in the mean obstructed defecation score 12 (from 10.6 to 2.9; p = 0.001) with the tRRems procedure. Compared with staRR, the tRRems procedure has the advantage of lower costs because it requires only 1 circular stapler.…”
Section: Technical Notesmentioning
confidence: 83%
“…[19][20][21] We have further modified the tRRems procedure to be used mainly in those patients with rectal intussusception, because it is a faster, simpler technique using 1 circular stapler that accepts a large volume of tissue without requiring any manual resection with a running suture of the anterior anorectal quadrant. the aim of the current study was to demonstrate the use of this modified stapling technique, which we call the apex technique, to treat patients with obstructed defecation caused by rectal intussusception and full rectal mucosal prolapse (see Video, Supplemental Digital Content 1, http://links.lww.com/DCR/a158).…”
Section: Technical Notesmentioning
confidence: 99%
“…-Sets (Ethicon Endo-Surgery, Norderstedt, Deutschland) durchführen, wobei zuerst eine segmentale bzw. semizirkuläre Vollwandresektion der Rektumvorderwand nationen existieren [22][23][24][25][26]. Generell werden die chirurgischen Therapieoptionen bei der Rektozele kontrovers diskutiert, wobei die Fokussierung auf eine Rektozele als singuläre Ursache der Entleerungsstörung häufig nicht zum therapeutischen Erfolg führt [22,23].…”
Section: Chirurgische Technik Der Starr-operationunclassified
“…We read with great interest the article by Leal et al [1] in which the authors concluded that the transanal repair of rectocele and rectal mucosectomy with a single circular stapler (TRREMS procedure) has satisfactory anatomic and functional results with a low incidence of postoperative pain and complications.…”
Section: Sirmentioning
confidence: 99%